1999
DOI: 10.1097/00003246-199910000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Continuous plasmafiltration in sepsis syndrome

Abstract: PF caused a significant attenuation of the acute-phase response in sepsis. There was no significant difference in mortality, but there was a trend toward fewer organs failing in the PF group that suggests that this procedure might be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(83 citation statements)
references
References 52 publications
2
81
0
Order By: Relevance
“…Nevertheless, it has been suggested that these therapies might be beneficial, especially for patients with Gram-negative sepsis [52,54,56,57] and when implemented as early as possible [58]. Additional studies are therefore warranted to better assess these therapies for blood purification [59].…”
Section: Plasmapheresis and Coupled Plasma Filtration Adsorptionmentioning
confidence: 99%
“…Nevertheless, it has been suggested that these therapies might be beneficial, especially for patients with Gram-negative sepsis [52,54,56,57] and when implemented as early as possible [58]. Additional studies are therefore warranted to better assess these therapies for blood purification [59].…”
Section: Plasmapheresis and Coupled Plasma Filtration Adsorptionmentioning
confidence: 99%
“…Current guidelines, for example, state that 'hemofiltration should not be used in patients with sepsis without renal indications unless ongoing studies provide positive results' [24]. The role of plasma exchange remains equally controversial [25,26]. In contrast, the initial findings with CPFA are consistent and provide provocative observations, which will no doubt encourage clinical investigators to further pursue the path of blood purification.…”
Section: Resultsmentioning
confidence: 99%
“…One randomized controlled trial of a limited number of subjects revealed a trend toward fewer failing organs but no effect on mortality with continuous plasmapheresis using a hollow-fiber plasma filter [14]. Another randomized clinical trial of 106 patients with septic shock found an all-cause mortality rate of 33.3% in the continuous flow plasmapheresis group and 53.8% in the control group, but imbalances in randomization favored the pheresis group [15].…”
Section: Increased Membrane Permeabilitymentioning
confidence: 99%